Organization of main structural autoantigens in autoimmune bullous dermatoses - Dmochowski, Marian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
In this review, the structure of type VII collagen, ß4 integrin subunit, laminin 5, desmosomal cadherin desmoglein 1, plakin BPAG1e, and BP180 was discussed. These proteins are widely believed to be the main structural autoantigens in autoimmune bullous dermatoses.